Current Chemistry Investigators (CCI): Development and Evaluation of a Scientist in a Classroom Electrochemistry Workshop - O'Donoghue, John; Garcia Domenech, Natalia; Mc Goldrick, Niamh (My University, 2023)
Over the course of the COVID-19 pandemic, school students suffered from a reduction in opportunities to connect with higher education institutions, meet scientific role models in person, discuss scientific career options, and carry out hands-on practical laboratory activities. Current Chemistry Investigators (CCI) is a successful electrochemistry-based STEM career intervention program, developed and evaluated through a co-creation process with teachers and students. The goals of CCI are 2-fold: first, to provide school students with career advice through tangible scientific role models and, second, to provide real-world context for the fundamentals of electrochemistry through hands-on activities. Herein, the development of a novel electro-analytical workshop from concept through to delivery with over a thousand students having taken part to date is reported. Students are tasked with solving why a battery malfunctioned through quantitative and qualitative analyses of an electrolyte using conductivity meters. Student feedback is also gathered anonymously through the use of a classroom response system (also known as “clickers”). Together with feedback from teachers, a robust evaluation is presented to measure the impact of providing tangible scientific role models and the usefulness of the workshop.
PUBLISHED
Keywords: Electrochemistry; Secondary Schools; Outreach Researchers; Digital Engagement; Inclusive Society; Smart & Sustainable Planet; Electrochemical energy conversion; Energy Storage Systems; Children; Education